Preliminary Reflections on Aspects of Holocaust-Era Litigation in American Courts - Burt Neuborne (Washington University Law Quarterly, 2002)
Aided by diplomatic initiative by Germany and the United States, any by the vigorous support of many political figures and community organizations, Holocaust-related litigation in American courts against Swiss, German, Austrian, and French corporations over the past six years has resulted in the assemblage of a vast pool of assets value din excess of 8 billion for distribution to Holocaust victims around the world. This article addresses the status of distribution efforts and considers certain aspects of the legal and moral issues raised by Holocaust litigation.
Keywords: Jewish Holocaust (1939-1945) – Reparations; Class actions (Civil procedure); Forced labor – Germany; Holocaust victims; War reparations; Germany; International; Switzerland